CONTINUITY AND CHANGE IN PUEBLOAN RITUAL PRACTICE: 3, 800 YEARS OF SHRINE USE IN THE NORTH AMERICAN SOUTHWEST. Issue 2 (21st March 2017) - Geib, Phil R.; Heitman, Carrie C.; Fields, Ronald C.D.
Abstract : Radiocarbon dates on artifacts from a Puebloan shrine in New Mexico reveal a persistence in ritual practice for some 3, 800 years. The dates indicate that the shrine had become an important location for ceremonial observances related to warfare by almost 2000 cal. B.C., coinciding with the time when food production was first practiced in the Southwest. The shrine exhibits continuity of ritual behavior, something that Puebloans may find unsurprising, but also changes in the artifacts deposited that indicate new technology, transformations of belief, and perhaps shifting cultural boundaries. After briefly describing this shrine, we discuss some of the artifacts that were deposited there, in particular atlatl darts and flat curved sticks with longitudinal facial grooves. We argue that both were used in ritual fights and then deposited in the shrine as offerings, establishing a behavioral tradition that set the precedent for ethnographic recognition of the site as an important war shrine. Atlatl darts are analogous with prayer sticks, the latter representing a derived form of this offering with arrows as an intermediary form. Flat curved sticks were used for defense against atlatl darts in duels that enhanced warrior status. Abstract : Los fechados radiocarbónicos de los artefactos procedentes de un santuario de los pueblo ancestrales en Nuevo México revelan que la práctica ritual en este sitio persistió durante unos 3, 800 años. Las fechas indican que el santuario se había convertido en un lugar importante para las prácticas ceremoniales relacionadas con la guerra hacia aproximadamente 2000 cal a.C., coincidiendo con la introducción de la agricultura en el suroeste de Estados Unidos. El santuario presenta continuidad en la conducta ritual, lo cual puede resultar poco sorprendente para los pueblo. Sin embargo, también se detectan cambios en los objetos depositados que indican nuevas tecnologías, transformaciones en las creencias y, tal vez, fronteras culturales cambiantes. Después de una breve descripción del santuario, se discuten algunos de los artefactos allí depositados, en particular los dardos de atlatl y los palos planos curvados con ranuras longitudinales faciales. Se argumenta que ambos fueron utilizados en peleas rituales y luego depositados en el santuario como ofrendas, estableciendo una tradición de comportamiento que asienta las bases para el reconocimiento etnográfico del sitio como un importante santuario de guerra. Los dardos de atlatl son análogos a los palos de oración: estos últimos representan una forma derivada de esta ofrenda, con las flechas como una forma intermedia. Los palos planos curvados fueron utilizados para la defensa contra los dardos de atlatl en duelos que aumentaban el estatus del guerrero.